2019
DOI: 10.1055/s-0037-1610405
|View full text |Cite
|
Sign up to set email alerts
|

40 Years of Hydrogen–Deuterium Exchange Adjacent to Heteroatoms: A Survey

Abstract: Deuteration of bioactive molecules is gaining more and more attention, especially after the approval of the first deuterated drug (Austedo™) by the US Food and Drug Administration (FDA). Not only is deuteration important for drug development, the amount of deuterium in a molecule is critical for the production of standards in mass spectrometry and the selectivity of the deuteration is mandatory for NMR applications. Very frequently, the molecules involved in these applications contain several heteroatoms. It h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(10 citation statements)
references
References 68 publications
0
8
0
2
Order By: Relevance
“…A great review presenting the possibility of pH dependent and metal-catalyzed hydrogen−deuterium exchange adjacent to the sulfur atom was presented by Michelotti and co-workers [115]. Rauk et al [116] demonstrated a deuteration process in the presence of NaOD in D 2 O or just in D 2 O for substances containing the methylsulfonyl or methylsulfinyl groups.…”
Section: Ph Dependent and Metal-catalyzed Hdx Adjacent To Sulfur Atommentioning
confidence: 99%
“…A great review presenting the possibility of pH dependent and metal-catalyzed hydrogen−deuterium exchange adjacent to the sulfur atom was presented by Michelotti and co-workers [115]. Rauk et al [116] demonstrated a deuteration process in the presence of NaOD in D 2 O or just in D 2 O for substances containing the methylsulfonyl or methylsulfinyl groups.…”
Section: Ph Dependent and Metal-catalyzed Hdx Adjacent To Sulfur Atommentioning
confidence: 99%
“…Deuterated organic compounds have been used as probes for mechanistic studies of biologically active compounds and pharmaceuticals and in chemical and biological processes 2–4 . Hydrogen–deuterium exchange (H–D exchange) is one of the methods used for preparation of deuterium‐labeled compounds 4–9 . The introduction of deuterium by H–D exchange is beneficial as the final step in the construction of bioactive compounds 10 .…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] Hydrogen-deuterium exchange (H-D exchange) is one of the methods used for preparation of deuterium-labeled compounds. [4][5][6][7][8][9] The introduction of deuterium by H-D exchange is beneficial as the final step in the construction of bioactive compounds. 10 Deuteration of aromatic amines and amides is of significant importance as many drug candidates are nitrogen-containing compounds.…”
Section: Introductionmentioning
confidence: 99%
“…The method features simple operation and mild reaction conditions, and a variety of aromatic aldehyde substrates could afford products with high deuterium incorporation. Keywords deuteration; deuteroxide; benzoin condensation; N-heterocyclic carbene; organocatalysis 氘( 2 H 或者 D)是氢( 1 H)安全、稳定的同位素, 氘代 化合物具有广泛的用途, 可用于核磁共振分析、反应机 理研究、材料科学和药物研发 [1][2][3][4] . 2017 年, 氘代丁苯那 嗪(SD-809)作为第一个氘代药物被美国食品药品监督管 理局(FDA)批准上市 [5] .…”
unclassified
“…2017 年, 氘代丁苯那 嗪(SD-809)作为第一个氘代药物被美国食品药品监督管 理局(FDA)批准上市 [5] . 氘代分子的制备主要有合成砌 块法、化学转化法和氢-氘交换方法(hydrogen deuterium exchange, HDE)等 [1][2][3][4]6] . 与传统的源于氘代合成砌块的 多步合成方法不同, HDE 反应不需要稀缺或昂贵的原 料, 一般采用常见的氘代溶剂或市售氘气作为氘源, 在 催化剂作用下发生反应, 简便易操作.…”
unclassified